2021
DOI: 10.1063/5.0050999
|View full text |Cite
|
Sign up to set email alerts
|

Impact and trends in embedding field programmable gate arrays and microcontrollers in scientific instrumentation

Abstract: Microcontrollers and field-programmable gate arrays have been largely leveraged in scientific instrumentation since decades. Recent advancements in the performance of these programmable digital devices, with hundreds of I/O pins, up to millions of logic cells, >10 Gb/s connectivity, and hundreds of MHz multiple clocks, have been accelerating this trend, extending the range of functions. The diversification of devices from very low-cost 8-bit microcontrollers up to 32-bit ARM-based ones and a system of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…A recent study showed that scientific equipment suppliers introduce more new-to-the-market product innovations than do other firms belonging to the same sectors and with similar characteristics, and that university demand is particularly important for explaining these differences (Bianchini et al 2019). The increased complexity of instruments (Carminati and Scandurra 2021), combined with black box designs and lack of interoperability (Hohlbein et al 2022) result in experimental settings that are extremely difficult to inspect and customize. Today, lack of access to equipment information is a barrier to innovation and collaborative work; when possible, teams dedicate already scarce research time to reverse engineering devices.…”
Section: Science Hardware Today: Centralization Dependency Inefficien...mentioning
confidence: 99%
“…A recent study showed that scientific equipment suppliers introduce more new-to-the-market product innovations than do other firms belonging to the same sectors and with similar characteristics, and that university demand is particularly important for explaining these differences (Bianchini et al 2019). The increased complexity of instruments (Carminati and Scandurra 2021), combined with black box designs and lack of interoperability (Hohlbein et al 2022) result in experimental settings that are extremely difficult to inspect and customize. Today, lack of access to equipment information is a barrier to innovation and collaborative work; when possible, teams dedicate already scarce research time to reverse engineering devices.…”
Section: Science Hardware Today: Centralization Dependency Inefficien...mentioning
confidence: 99%
“…Traditional desktop computers are no longer able to meet the requirements of many modern applications, which require such features as portability, low latency, parallelization, reconfigurability, networking, multi-platform compatibility, distributed processing, and low cost. In recent years, embedded systems based on microcontroller units (MCUs), digital signal processors (DSPs), or field programmable gate arrays (FPGAs) have been increasingly used in scientific instruments, especially in the AFM [ 9 ]. For example, Wong et al proposed an STM and AFM control system with an open architecture based on AT&T’s DSP32C DSP, which not only greatly simplifies the complex AFM system but also makes it possible to achieve functions that were not easy or impossible to achieve with analog electronic equipment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation modules of the first generation of RFSoC chips have been used to demonstrate their applicability to quantum computation [8][9][10][11][12] . FPGA devices have been used quite extensively in scientific experiments 13 and there are many examples of their use for readout and control of superconducting qubits [14][15][16][17] . The RFSoC platform differs significantly from this previous use of FPGAs because the on-chip integration of high-speed data converters enables direct digital synthesis (DDS) of RF waveforms.…”
Section: Introductionmentioning
confidence: 99%